Physico-chemical parameters and culturable yeast diversity in surface water: a consequence of pollution - Mzimkhulu Monapathi; Carlos Bezuidenhout; Owen Rhode (Water SA, 2020)
Rivers in the North West Province (NWP) of South Africa are polluted by various anthropogenic activities that are associated with agricultural, domestic, industrial, and mining activities. Pollutants and effluent resulting from these activities impact the physico-chemical and biological characteristics of river water. More particularly, domestic and agricultural pollution has been associated with the occurrence of pathogenic yeast species in water. The aim of this study was to determine physico-chemical parameters, yeast levels, and the antifungal susceptibility of pathogenic yeasts in river water. Physico-chemical parameters and yeast levels were determined using standard procedures. Yeasts were identified by biochemical tests and 26S rRNA gene sequencing. Disc diffusion antifungal susceptibility tests were conducted on identified potential pathogenic yeasts. Physico-chemical parameters were within target water quality ranges (TWQR) for livestock farming but were mostly out of range for irrigation. Yeast levels (incubation at 37°C) ranged from 363 to 1 778 CFU/L. There were significant differences (p < 0.05) in the physico-chemical parameters and yeast levels between some seasons and among the river systems under study. A positive association was observed between temperature, COD and yeast levels in all the river systems. Ascomycetes, which were the most prevalent isolates, were identified as Candida spp. (35%), Pichia spp. (13%), Cyberlinera spp. (12%), Meyerozyma spp. (11%), Clavispora spp. (10%), Saccharomyces spp. (6%), Kluyveromyces spp. (5%), Yamadazyma spp. (4%), Trichosporon spp. (3%), and Wickerhamomyces spp. (1%). Antifungal resistance of the potential pathogenic yeasts was as follows: flucytosine and miconazole (100%) > fluconazole (78.5%) > econazole, and miconazole and ketoconazole (49.6%) > nystatin (15.2%). The river water systems explored in the study are used for agricultural, domestic and recreational purposes. Direct contact with the water, especially by immune-compromised people, may pose a health threat and should be further investigated.